The tananá [Chlorocoelus hypericifolius (Stoll 1813): Orthoptera, Tettigonioidea, Pseudophyllinae]—re-discovered more than 150 years after the description of the male by Bates and the figuring by Darwin - Heller, Klaus-Gerhard; Helb, Matthias (Zootaxa, 2024)
In his famous book, “The descent of man and selection in relation to sex,” Darwin (1871) described the male secondary sexual characters of Orthoptera in some detail. As the most prominent example, he presented a figure of a South American bush-cricket species. It had been described a few years before by Bates and was called, onomatopoetically, Chlorocoelus tanana. Surprisingly, the fascinating species has never been found since this time, although in old collections some additional specimens were located. Based on recently collected material and information on the internet, we clarify the taxonomy of the species and give details of the male stridulatory organ and its distribution. The peak frequency (2.1 kHz) of its resonant disturbance sounds indicates that also calling song may have an unusually low carrier frequency similar to other large bush-crickets with extraordinarily inflated tegmina.